2016
DOI: 10.1108/ijlm-11-2014-0175
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of business uncertainty on supply chain integration

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 94 publications
(146 reference statements)
3
38
1
Order By: Relevance
“…A significant stream of research has pertained to a higher level of SC integration with increased SC responsiveness and superior performance. Kim and Chai (2016) identified business uncertainty as the primary cause of raising the need to explore and evaluate each type of SC integration for survival in highly competitive environments, while Zhu et al (2017) identified SC integration as a risk management strategy. Frohlich and Westbrook's (2001) presented a framework of "arcs of integration" which conceptualizes customers and suppliers' integration and measured performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A significant stream of research has pertained to a higher level of SC integration with increased SC responsiveness and superior performance. Kim and Chai (2016) identified business uncertainty as the primary cause of raising the need to explore and evaluate each type of SC integration for survival in highly competitive environments, while Zhu et al (2017) identified SC integration as a risk management strategy. Frohlich and Westbrook's (2001) presented a framework of "arcs of integration" which conceptualizes customers and suppliers' integration and measured performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreso, Xu, Huo and Sun (2014) penned significant relationship between intra-organizational variable such top management support (TMS) and information technology (IT) influence supply chain integration (supplier and customer; information and involvement), which eventually affect business performance, even though both supplier and customer collaboration exert their influence in different ways. Kim and Chai (2016) reveal a positive relationship between internal and external chain collaboration on firms performance especially where changes in the market (dynamisms) and competition in the market (hostility) are very intense. Additionally, Cui and Wu (2016) postulate that SCC (firm-customer)ensures dissemination of important knowledge and information on product and process, which can lead to improvement in productivity product quality as well as market share.…”
Section: Supply Chain Collaboration and Organizational Performancementioning
confidence: 98%
“…Much of the work within this line examines, either theoretically (Garavelli 2003;Sawhney 2006) or through case studies (Scavarda et al 2015;Simangunsong et al 2016), how match the different flexibility strategies adopted by SC partners in response to various types of business uncertainties (Candace et al 2011). The limited quantitative studies explore either the direct (Wang et al 2006;Nagarajan et al 2013;Kim and Chai 2016) or the moderating (Wong et al 2011;Qu et al 2014) effects of business uncertainty on the MSCF-performance relationship, as well as the development of MSCF capability to respond to dynamic and turbulent environments (Zhang et al 2005;Lim et al 2010;. Theoretically, these quantitative studies tend to build on contingency theory (Wong et al 2011;Kim and Chai 2016) or Resource Based View (Zhang et al 2005;Sawhney 2006;Nagarajan et al 2013).…”
Section: Figure 4 About Herementioning
confidence: 99%
“…The limited quantitative studies explore either the direct (Wang et al 2006;Nagarajan et al 2013;Kim and Chai 2016) or the moderating (Wong et al 2011;Qu et al 2014) effects of business uncertainty on the MSCF-performance relationship, as well as the development of MSCF capability to respond to dynamic and turbulent environments (Zhang et al 2005;Lim et al 2010;. Theoretically, these quantitative studies tend to build on contingency theory (Wong et al 2011;Kim and Chai 2016) or Resource Based View (Zhang et al 2005;Sawhney 2006;Nagarajan et al 2013). This stream highlights the importance of matching flexibility strategies to the business uncertainty experienced (Candace et al 2011;Fayezi et al 2014).…”
Section: Figure 4 About Herementioning
confidence: 99%
See 1 more Smart Citation